Construction drawings and details for interiors : basic skills - Kilmer, W. Otie.; Kilmer, Rosemary (Hoboken, New Jersey : Wiley, 2009)
Construction Drawings and Details for Interiors serves as the essential reference for designers preparing interior construction documents, explaining how to do a new construction, remodeling, or installation project. In a highly visual format, the book covers drafting fundamentals and conventions; drawing types, plans, and schedules; and computer-aided design (CAD). With expanded coverage of the preparation and communication of construction documents in digital formats, drawing interior perspectives, and more, the text also serves as an invaluable study reference for the contract documents section of the NCIDQ exam. A new companion Web Site supplies template grids for schedules and contract documents for practice exercises.
Part I. Drawing communication, equipment, fundamentals, and classification systems : Drawing as communication -- Drafting equipment and their care -- Drawing and drafting fundamentals -- Drawing classification systems -- Part II. Contract documents : Construction drawings, specifications, and contracts -- As-built drawings and demolition plans -- Floor plans -- Fire and life safety plans -- Elevations -- Sections -- Specialty drawings -- Door and window schedules -- Finish schedules and finish plans -- Furniture installation plans -- Furnishings and equipment plans -- Reflective ceiling, lighting, and electrical plans -- Mechanical and plumbing plans -- Reproduction methods and computers -- App.A. Example numbering for simple interior project table of contents -- App.B. MasterFormat, 2004 edition level 1 and 2 numbers and titles -- App.C. Sample ADA guidelines -- App.D. Abbreviations for construction drawings.
Includes index.
Keywords: BUILDING